Analisis Pengaruh Upah Minimum, Tingkat Pendidikan Dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan Di Provinsi Bali Periode Tahun 1995-2012 - Wiradinata, Kadek Ivan; Kartika, Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 6, Juni 2015 (pp. 608 - 745), 2015)
This study aimed to determine the effect of the minimum wage, the level of education and unemployment rate to the level of poverty in the province of Bali. The data used in this study are secondary data drawn from the Central Statistics Agency (BPS) of Bali from 1995 - 2012. Data were analyzed by multiple linear regression. The results of the study indicate that the minimum wage and the level of education has a negative effect on poverty, while the unemployment rate has a positive effect on the level of poverty.
Keywords: tingkat kemiskinan, upah minimum, tingkat pendidikan, tingkat pengangguran